Average Based Length Fuzzy Time Series Data Seasonal untuk Prediksi Volume Impor Migas Indonesia - Adika Setia Brata; Alfian Anhar; Windy Lestari; Melda Juliza; Suci Rahmawati; M Tantry Abeng Evan Nugroho (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2021)
This study aims to predict the value of Indonesian oil and gas imports using the Fuzzy Time Series method of determining average-based intervals (Average Based Length). The data used in this research is annual periodic data from 2013-2021 which was downloaded from the bps.go.id website. The research results show that the volume value of oil and gas imports in Indonesia in January 2023 will reach 4125,802 thousand tons. This research can be concluded that the accuracy of the estimation is very good, producing a MAPE value of 8.04%. The MAPE value is defined as having very good estimation results if the MAPE value is <10%.